Pengaruh Penambahan Sargassum sp. dan Inositol dalam Pakan terhadap Pertumbuhan dan Daya Tahan Juvenil Ikan Gurami (Osphronemus gouramy Lac.) - Lestari, Dwi; Widiastuti, E. L.; Nurcahyani, N.; Susanto, G. N. (Jurnal Natur Indonesia, 2016)
Gourami (Osphronemus gouramy Lac.) as one of the freshwater fishes, are easily to be cultured but slow in growth rate. One of the ways to enhance their growth rate is by feeding them with high nutritious food. Sargassum sp. and inositol are known compound able to stimulate the growth of some fishes. The study was conducted to determine the effect of Sargassum sp and inositol on commercial feed to the growth rate and survival of juvenile gouramy. The study was conducted from January to April 2015 in Aquatic Laboratory of Biology Department - University of Lampung. Completely randomized designed was used with 4 treatment groups and 5 replications. Anova and Tukey at 5% levels were applied to this study. The result indicated that addition of inositol and Sargassum sp on commercial food significantly affected the gourami growth parameters such as the body weight, body length, body width as well as juvenile gouramy spesific growth rate and their survival rate.